2012
DOI: 10.1111/j.1747-6593.2012.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects and modelling of ultrasonic waste‐activated sludge disintegration

Abstract: Sonication is a well-known sludge pretreatment technique with the advantages of simple operation and high efficiency. However, it is an energy-intensive process. Hence, it is very important to predetermine its sludge disintegration efficiency at varying pretreatment conditions in order to minimize the ultrasonic energy consumption. In this study, it was found that the ultrasonic sludge disintegration occurred in two stages: rapid and subsequent slow disintegration stages. For this reason, it was aimed to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Li et al (2008) confi rmed high effectiveness of alkaline conditioning by sodium hydroxide (dosage of 0.2 g/g VS), aided by ultrasonic fi eld (ultrasonic pre-treatment). Şahinkaya and Sevimli (2013) achieved sludge disintegration of 24.4% after using only NaOH as a disintegrating agent. Kim et al (2003) Similar results were obtained by Wonglertarak and Wichitsathian (2014), They concluded that the SCOD increased when pH values were increased.…”
Section: Introductionmentioning
confidence: 97%
“…Li et al (2008) confi rmed high effectiveness of alkaline conditioning by sodium hydroxide (dosage of 0.2 g/g VS), aided by ultrasonic fi eld (ultrasonic pre-treatment). Şahinkaya and Sevimli (2013) achieved sludge disintegration of 24.4% after using only NaOH as a disintegrating agent. Kim et al (2003) Similar results were obtained by Wonglertarak and Wichitsathian (2014), They concluded that the SCOD increased when pH values were increased.…”
Section: Introductionmentioning
confidence: 97%
“…Only few studies focus on developing mathematical models for ultrasonic treatment (e.g., Li et al, 2010;Sahinkaya and Sevimli, 2012) and if they do, they do not consider the ultrasonic treatment in combination with the conventional activated sludge processes since their main interest is optimizing and improving the efficiency of the ultrasonic activated sludge treatment prior to sludge anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the ultrasonic density increased to 1.3 -2.5 W/mL, the CST rate increased rapidly, leading to a decrease in sludge dewaterability and solids content. Serkan et al conducted experiments on sludge dewatering characteristics and found that the optimal ultrasonic density was 0.75 -1 W/mL (specific energy consumption of 60000 kJ/kg TS) [7]. When the ultrasonic density increased above 1.2 W/mL or below 0.5 W/mL, the CST level increased significantly and the sludge dewaterability decreased.…”
mentioning
confidence: 99%